Training on Preparation of Village Fund Financial Reports for Village Apparatus in Mangunreja Village - Mira Nurhikmat; Enji Azizi; Yulaikah Yulaikah (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The attention of the state in developing villages is unquestionable. Evidence of the seriousness of the state in developing villages is manifested by the issuance of Village Law no. 6 of 2014 and Village Government Regulation No. 43 of 2014. These two legal regulations provide an opportunity for all villages in Indonesia to obtain a Village Fund of 1 billion originating from the Village Fund from the Central Government 750 million and Village Fund Allocations at the Provincial and Regency/Municipal levels. City of 250 million. Village funds provided by the central government aim to encourage the productivity of rural communities. For this reason, the use of village funds must be planned, implemented, and reported to assess the level of success of the village fund program. To make this village fund program a success, the community service team of the Management Study Program of the Faculty of Economics and Business held "Training for Preparation of Village Fund Financial Reports for Village Apparatus in Mangunreja Village". The objectives of the PkM activities for the Preparation of Village Fund Financial Reports for Village Apparatus are to 1). Provide adequate knowledge regarding Village Fund financial reporting and 2). Provide training to make Village Fund financial reports.